Large Scale Scientific Modeling Practices That Can Organize Science Instruction at the Unit and Lesson Levels - Nunez-Oviedo, Maria Cecilia; Clement, John J. (Frontiers in Education, 2019)
Science educators today still struggle with finding better ways to help students develop strong conceptual understandings as opposed to memorizing isolated facts. Recently there has been increased attention on learning explanatory models as a key to conceptual understanding. Science educators also struggle with how to teach students scientific thinking practices, and sometimes this goal is seen as being in competition with content goals for conceptual understanding. In this study we ask whether whole class discussion can contribute to both of these goals at the same time and whether there are ways that a teacher can support this. We describe the results of a case study of an experienced teacher leading modeling discussions in a series of three middle school life sciences classes. A qualitative microanalysis of the videotaped whole class discussions led to the identification of a variety of modeling processes operating across the lessons at two different time scale levels. These include model competition, in which students compare and evaluate their models, and model evolution, in which the models go through stepwise evaluation and improvement. The latter process involves a smaller time scale pattern of model generation, evaluation, and modification cycles. All of these processes are similar to those found in recent studies of practices of expert scientists. Implications from the case study suggest that: (1) A teacher need not be limited to the two opposing interaction styles of Open Discussion vs. Authoritative lecture. Rather, there are there intermediate discussion styles between these that involve co-construction and cognitive scaffolding; (2) It is possible to start from student-generated models that conflict with the target model in a number of ways, and still arrive at the target model for the lesson through discussion. Processes of model competition and disconfirmation, as well as model evolution, both supported by the teacher's cognitive scaffolding, were central in this accomplishment; (3) In doing so, it is possible for a teacher to foster student modeling practices, as a type of scientific thinking, at the same time that they are teaching science content. Number of words: 12084 (permission granted by Ian Hargreaves to be slightly over 12000)